2014
DOI: 10.1097/coc.0b013e31826b9950
|View full text |Cite
|
Sign up to set email alerts
|

Reirradiation for Locoregionally Recurrent Lung Cancer

Abstract: Objectives To our knowledge this is the largest report analyzing outcomes for reirradiation (reRT) for locoregionally recurrent lung cancer, and the first to assess thoracic reRT outcomes in patients with small cell lung cancer (SCLC). Methods Forty-eight patients (11 SCLC, 37 non–small cell lung cancer [NSCLC]) receiving reRT to the thorax were identified; 44 (92%) received reRT by intensity-modulated radiotherapy. Palliative responses, survival outcomes, and prognostic factors were analyzed. Results NSCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Kim described 10 patients who underwent re-irradiation for locally recurrent esophageal cancer following definitive radiotherapy, and the 2 patients who had long times to recurrence (17.8 and 36.4 months) had a complete response [17]. This finding has also been reported in many studies of other tumors [14, 16, 21]. However, Hong failed to show the association between survival and time to recurrence [12], probably because the study included patients with mixed patterns of recurrence, including those with regional lymph node recurrence only, local failure or both.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Kim described 10 patients who underwent re-irradiation for locally recurrent esophageal cancer following definitive radiotherapy, and the 2 patients who had long times to recurrence (17.8 and 36.4 months) had a complete response [17]. This finding has also been reported in many studies of other tumors [14, 16, 21]. However, Hong failed to show the association between survival and time to recurrence [12], probably because the study included patients with mixed patterns of recurrence, including those with regional lymph node recurrence only, local failure or both.…”
Section: Discussionmentioning
confidence: 68%
“…A higher re-RT dose has been recommended for recurrent lung cancer, nasopharyngeal carcinoma and other tumors and has been shown to lead to an increase in local control and survival [1416]. However, the optimal re-RT dose in patients with recurrent ESCC following definitive radiotherapy remains uncertain, although the importance of re-RT is well known.…”
Section: Discussionmentioning
confidence: 99%
“…Published data have suggested that either thoracic re-RT with conventional fractionation [ 8 10 , 19 , 20 ] or with SBRT [ 5 – 7 , 11 14 ] is a reasonable treatment option to consider for relapse or progression. However, there is a lack of prospective evidence detailing outcomes after thoracic re-RT.…”
Section: Discussionmentioning
confidence: 99%
“…The longer interval group (≥16 months) had a better prognosis than the shorter interval group (< 16 months). In studies of re-irradiation for lung cancer, it has been reported that a longer interval between the first RT and re-irradiation was associated with better survival (26, 27). A multi-institutional cohort study of re-irradiation for head and neck tumors indicated that more than a 2-year interval from the first RT to re-irradiation is a factor indicating better prognosis (28).…”
Section: Discussionmentioning
confidence: 99%